Identification of dynamic displacements and modal frequencies of amedium-span suspension bridge using multimode GNSS processing - Yu, Jiayong; Meng, Xiaolin; Shao, Xudong; Yan, Banfu; Yang, Lei (Elsevier, 2014)
Global Navigation Satellite System (GNSS) positioning technology has been employed in the dynamic monitoring of long-span bridges in the recent years. However, it has difficulties to meet the higher accuracy requirements of the dynamic monitoring of small or medium span bridges, due to the presence of measurement noise from multipath, cycle slips, ionosphere delay, orbital errors, etc. To verify the feasibility of using current GNSS technology to monitor these bridges, a series of monitoring experiments have been carried out on the Wilford suspension bridge in Nottingham (UK) with GNSS and a triaxial accelerometer. Three GNSS data processing modes, i.e. Real-Time Kinematic (RTK), network RTK and Post-Processing Kinematic (PPK), were considered. An innovative multimode adaptive filtering (MAF) that combining adaptive filter with Chebyshev highpass filter was used to identify the dynamic displacements of the bridge from the multimode GNSS data. To validate the GNSS results, the dynamic displacements were also computed from double integration of the accelerometer-measured accelerations. The differences of the displacements between the GNSS and accelerometer results were obtained. The standard deviation and the mean deviation of these differences are less than 1 mm, which is good enough for the monitoring purposes. The modal frequencies of the bridge can be accurately identified from GNSS measurements, and successfully validated by those from the accelerometer data. Using the multimode GNSS data and the proposed the MAF algorithm, with sub-millimeter level accuracy GNSS can be used to monitor the vibration response of small or medium span bridges as well as long-span bridges.